2021
DOI: 10.1039/d1qo01189h
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed [1,3]-alkoxy rearrangement for the selective synthesis of polycyclic ortho-aminoarenol derivatives

Abstract: Copper-catalyzed [1,3]-alkoxy rearrangement reactions of polycyclic arenes, such as naphthalenes and phenanthrenes, proceeded efficiently to afford the corresponding ortho-aminoarenol derivatives in good to excellent yields. Through the appropriate choice of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[5] We recently reported that N-alkoxyanilines efficiently underwent [1,3]alkoxy rearrangement reactions in the presence of Nheterocyclic carbene (NHC)-ligated cationic Cu catalysts. [6][7][8][9][10] In particular, [1,3]-alkoxy rearrangement of N-methoxyanilines 1, which have an electrondonating group (EDG), such as an alkyl or an electronrich aryl group, at the ortho position underwent domino [1,3]/ [1,2] rearrangement reactions to afford 3substituted 2-anisidines 2 (Scheme 1a). [7][8][9][10] According to our mechanistic studies including our recent research on the NÀ O bond cleavage, [11] we propose that the reaction is initiated by oxidative addition of NÀ O bond to the cationic Cu catalyst to form the tetracoordinated cationic alkoxycopper(III) complex A.…”
Section: Introductionmentioning
confidence: 99%
“…[5] We recently reported that N-alkoxyanilines efficiently underwent [1,3]alkoxy rearrangement reactions in the presence of Nheterocyclic carbene (NHC)-ligated cationic Cu catalysts. [6][7][8][9][10] In particular, [1,3]-alkoxy rearrangement of N-methoxyanilines 1, which have an electrondonating group (EDG), such as an alkyl or an electronrich aryl group, at the ortho position underwent domino [1,3]/ [1,2] rearrangement reactions to afford 3substituted 2-anisidines 2 (Scheme 1a). [7][8][9][10] According to our mechanistic studies including our recent research on the NÀ O bond cleavage, [11] we propose that the reaction is initiated by oxidative addition of NÀ O bond to the cationic Cu catalyst to form the tetracoordinated cationic alkoxycopper(III) complex A.…”
Section: Introductionmentioning
confidence: 99%
“…Against this backdrop, we designed cascade reactions, including the Cu-catalyzed [1,3]-rearrangement, as a potential approach to overcome issues related to selectivity ( Figure 3 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. We have recently reported that N -heterocyclic carbene (NHC)-ligated cationic copper catalysts efficiently promote the [1,3]-rearrangement of N -alkoxyanilines [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although other approaches to functionalized meta-aminophenol derivatives have been recently reported [22], the development of efficient and robust methods for the synthesis of multiply substituted meta-aminophenol derivatives is a pressing issue. Against this backdrop, we designed cascade reactions, including the Cu-catalyzed [1,3]-rearrangement, as a potential approach to overcome issues related to selectivity (Figure 3) [23][24][25][26][27][28][29][30][31][32]. We have recently reported that N-heterocyclic carbene (NHC)-ligated cationic copper catalysts efficiently promote the [1,3]-rearrangement of N-alkoxyanilines [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations